Platelet-rich fibrin – contemporary approach in aesthetic medicine and dentistry (Journal of Face Aesthetics, 2023)
Introduction and aim. In recent years, there has been an increasing popularity in the use of platelet‑rich fibrin (PRF) in maxillofacial surgery and aesthetic medicine. This article presents a review and summary of current medical literature regarding the applications of this preparation in these fields.Material and methods. A systematic review of current English‑language medical literature was conducted using the PubMed database, using the search phrases „PRF”, „platelet‑rich fibrin in aesthetic medicine”, and „platelet‑rich fibrin in dentistry”.Results and conclusions. PRF, as an autologous, inexpensive, and easily obtainable preparation that can be applied in many aesthetic medicine and dental procedures, may play a significant role in the future of these medical fields. However, in the coming years, attention should be paid to conducting more detailed studies on the effects of this therapy, as most of the previous research has been based on small patient groups, with short follow‑up periods or containing errors in the research design.
Keywords: platelet-rich fibrin; PRF; aesthetic medicine